2020
DOI: 10.1213/ane.0000000000004346
|View full text |Cite
|
Sign up to set email alerts
|

To Infinity and Beyond: The Past, Present, and Future of Tele-Anesthesia

Abstract: Because the scope of anesthesia practice continues to expand, especially within the perioperative domain, our specialty must continually examine technological services that allow us to provide care in innovative ways. Telemedicine has facilitated the remote provision of medical services across many different specialties, but it remains somewhat unclear whether the use of telemedicine would fit within the practice of anesthesiology on a consistent basis. There have been several reports on the successful use of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 37 publications
0
29
0
Order By: Relevance
“…The application of telemedicine to the field of anesthesiology and perioperative medicine is still in its nascency with significant potential to impact patient outcomes and satisfaction. 10 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The application of telemedicine to the field of anesthesiology and perioperative medicine is still in its nascency with significant potential to impact patient outcomes and satisfaction. 10 …”
Section: Discussionmentioning
confidence: 99%
“… 2 Subsequent studies have likewise found high patient and provider satisfaction with no increase in day-of-surgery (DOS) cancellations when using telemedicine for preoperative assessment. 3 - 12 Furthermore, patients who underwent telemedicine evaluation were found to save significant time, distance, and cost associated with travel and in some cases, a shorter duration of the evaluation itself. 4 , 6 , 9 , 13 These savings were found both in rural and metropolitan settings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The application of telemedicine to perioperative care maybe the most obvious evidence of how consumer technology influences anaesthesia practice. [ 31 ] Anaesthesia information management systems (AIMS) are becoming more widely used, and there is increased interest in using AIMS data for intraoperative clinical decision support (CDS). The possible benefits of CDS for anaesthesia include better patient safety, billing accuracy, and compliance.…”
Section: Research In Anaesthesiology and Critical Carementioning
confidence: 99%
“…The adoption of telehealth for preoperative evaluation clinics has gained some traction to reach patients who may not otherwise present to a clinic [5,6]. Patients who require multiple short visits for preoperative optimization, such as those enrolled in smoking cessation [7] or weight loss [8] programs have shown benefit from telehealth visits.…”
Section: Introductionmentioning
confidence: 99%